WEBSITE PROMOTION AND PROTECTION OF INTELLECTUAL PROPERTY: A SPANISH LAW PERSPECTIVE - Jiménez, David López (Law, State and Telecommunications Review, 2019)
Purpose ”“ The aim of this article is to analyse actions to promote websites that can violate intellectual property rights, in other words, copyright and the rights of online commercial brands. Methodology/approach/design ”“ An analysis of Spanish legislation on intellectual property rights. Findings ”“ Service providers that advertise on Internet deploy increasingly aggressive advertising formats which, on occasions, violate intellectual property rights. Spanish law on brands and unfair competition provides effective tools to sanction the various types of infraction that occur on Internet. This legislation could also be supported by industry self-regulation. Practical implications ”“ The analysis in this article can be of considerable use to all actors who operate in this setting (society, and the public and private sectors). Originality/value ”“ This article analyses the infractions that occur in advertising in relation to meta-labels and online links.